Changes in Textural Quality and Water Retention of Spiced Beef under Ultrasound-Assisted Sous-Vide Cooking and Its Possible Mechanisms - Hengpeng Wang; Ziwu Gao; Xiuyun Guo; Sumin Gao; Danxuan Wu; Zongzhen Liu; Peng Wu; Zhicheng Xu; Xiaobo Zou; Xiangren Meng (Foods, 2022)
The present study investigated the effects of ultrasound (28 kHz, 60 W at 71 °C for 37 min) combined with sous-vide cooking (at 71 °C for 40, 60, 80, 100, 120 min) on the textural quality, water distribution, and protein characteristics of spiced beef. Results showed that the spiced beef treated with conventional cooking (CT) had the highest cooking loss (41.31%), but the lowest value of shear force (8.13 N), hardness (55.66 N), springiness (3.98 mm), and chewiness (64.36 mJ) compared to ultrasound-assisted sous-vide (USV) and sous-vide cooking (SV) groups. Compared with long-time thermal treatment, USV heating within 100 min enhanced the water retention of spiced beef by maintaining the lower values of cooking loss (16.64~25.76%), T2 relaxation time (242.79~281.19 ms), and free water content (0.16~2.56%), as evident by the intact muscle fibers. Moreover, the USV group had relatively lower carbonyl content, but higher sulfhydryl content compared to CT and SV groups. More protein bands coupled with a minor transformation from α-helixes to β-turns and random coils occurred in USV40~USV80. In conclusion, these results indicated that USV treatment within 100 min positively affected the textural quality and water retention of spiced beef by moderate protein oxidation.